Analisis Sisa Makanan terhadap Kepuasan Pelayanan Makanan pada Pasien Rawat Inap di Rumah Sakit Islam Jemursari Surabaya - Rizki Hayyu Lestari; Putri Ramadhani Ayuningtyas; Azizah Ajeng Pratiwi; Agung Prasetyo (Media Gizi Kesmas, 2023)
Background: The amount of food waste from patients in the hospital represents less than optimal feeding, so food waste can be used as one indicator to evaluate the success of nutrition services in the hospital. High scores of food waste can result in inadequate nutrition intake until malnutrition in hospitalized patients. Objectives: The purpose of writing this article is to analyze food waste and food service satisfaction in inpatients. Methods: Descriptive research with cross sectional study design. The sampling method in this study was simple random sampling, with a total sample of 30 patients. This study used the dependent variable is food service satisfaction in inpatients and the independent variable is food waste in inpatients in the form of staple foods, animal side dishes, vegetable side dishes, vegetable. The data collection instruments for this research were observation of food waste, satisfaction survey questionnaires, and interviews with the head of the nutrition installation. Results: This study found that the highest average percentage of food waste for inpatients was in staple foods (28%) and the least in animal side dishes (12.5%). Food waste in elderly patients (45.83%) and children (39.28%) is high when compared to the standard limit is â‰¤20%. Most of the patients complained that the food served at the hospital was less attractive, the portions were too large, the temperature was cold, and the food was less varied. Conclusions: The food waste of inpatients in the elderly and children at Islam Jemursari Hospital Surabaya is still relatively high, so efforts are needed to improve nutrition services. Evaluation and improvement in the quality of service for the provision of food in hospitals can reduce food waste and increase patient satisfaction.